Correlations of vascular cognitive impairment with brain-derived neurotrophic factor and trace elements - Zhou Rong; Lei Chao; Zhi Haiyang (Romanian Journal of Laboratory Medicine)
Cognitive impairment has become one of the major public health problems due to population aging and the increased morbidity associated with stroke. In this study, we aimed to analyze the correlations of vascular cognitive impairment (VCI) with brain-derived neurotrophic factor (BDNF) and trace elements.